2012
DOI: 10.1002/ange.201200069
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Carbene Polymerization with Oxygenated Rh(diene) Species

Abstract: Scheme 1. Rh-catalyzed carbene polymerization.Scheme 2. Likely structures of 3 formed by oxidation of 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…ization above 0 8 8Cl ikely through a1 ,2-shift of the methyl group. [19] This reaction is irreversible,w hich is in agreement with experimental [3,4] and computational [20] data on many other systems where the insertion of ac arbene into M À C bonds is facile.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…ization above 0 8 8Cl ikely through a1 ,2-shift of the methyl group. [19] This reaction is irreversible,w hich is in agreement with experimental [3,4] and computational [20] data on many other systems where the insertion of ac arbene into M À C bonds is facile.…”
Section: Methodssupporting
confidence: 82%
“…[2] We were able to show that the key step responsible for C À Cb ond formation and cleavage is the formation of ac arbene complex through double CÀHa ctivation;t his intermediate is responsible for CÀCb ond formation and cleavage by migratory insertion or deinsertion of the carbene moiety into an IrÀCb ond (Scheme 1). Although the forward reaction in Scheme 1h as numerous precedents for various metals, [3,4] theonly detailed kinetic study was reported over three decades ago for niobocene derivatives. [5] Moreover,a nd to the best of our knowledge,t he reverse reaction, namely the deinsertion of acarbene from aC(sp 3 )ÀC(sp 3 )bond (or,inother words,the a-elimination of an alkyl group), has previously never been reported for unstrained substrates;t he corresponding aelimination of hydrogen, however,iswell known.…”
mentioning
confidence: 99%
“…Coordination and insertion of the CC bond of the substrate leads to a β‐hydroxy‐alkyl intermediate. Subsequent β‐hydroxy elimination14 and intramolecular deprotonation of the acidic allylic CH bond15 by the hydroxo ligand then leads to formation of 1 b with elimination of water.…”
Section: Methodsmentioning
confidence: 99%
“…By far, this approach results in the highest molecular weights published on C1 polymers via transition metal catalysis. With respect to the investigated monomer scope of C1 polymerization techniques, benzyl 2‐diazoacetate and ethyl 2‐diazoacetate have been most frequently used and polymers were obtained in good yields and high molecular weights, that is, 85% yield and 590000 g/mol ( M w ) for poly(ethyl 2‐ylidene‐acetate) . Polyolefins and their structural analogues polymethylenes, originating from carbene precursors as monomers, are highly important polymeric materials.…”
Section: Introductionmentioning
confidence: 99%